Implementation of the Game Development Life Cycle Method in Developing a Drag and Drop Educational Game for Traditional Indonesian Houses - Aulia Khoirunnita; Awang Harsa Kridalaksana; Adlina Safa Sephia Putri (Poltanesa, 2025)
Indonesia is renowned for being a country rich in culture, one aspect of which is reflected in the diverse traditional houses found across its regions. Unfortunately, younger generations are becoming less familiar with this heritage due to monotonous and theoretical approaches in formal education. To address this issue, this study aims to develop an Android-based educational game that utilizes a drag-and-drop concept to introduce Indonesia’s traditional houses interactively. The game development process follows the Game Development Life Cycle (GDLC), consisting of six main stages: initiation, pre-production, production, testing (black box), beta testing, and release. Data were collected through a literature review of traditional houses, the GDLC method, and educational game development techniques. The resulting game, titled "Kiddo Match It! Traditional Houses," features an interactive map of Indonesia, an encyclopedia of traditional houses, a series of levels based on geographic regions, and a gameplay mechanic that involves matching images of traditional houses with their names. All stages of GDLC were implemented with a focus on visually engaging design and user-friendly navigation, specifically for users aged 8–15 years. Black box testing showed that most features functioned as intended, while beta testing indicated a user satisfaction rate of 91%, categorized as “Very Good.” This study produced a digital learning medium that introduces 34 traditional houses from all Indonesia provinces through a visual and interactive approach, making it a relevant educational tool for cultural preservation in today’s digital era.